2012
DOI: 10.18553/jmcp.2012.18.8.627
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Success of Mailed Letter Intervention Programs to Influence Prescribing Behaviors: A Review

Abstract: BACKGROUND: Educational interventions have long been used as a means of influencing prescribing behavior. Various techniques including educational mailings, academic detailing, prescriber feedback with or without disclosing patient-identifying data, and supplemental patient information have been used to promote appropriate prescribing habits, reduce costs, and optimize patient care. While the effects of educational intervention programs are widely reported, little information is available regarding the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…In this study, we demonstrated that mailed personalised feedback could lead to meaningful changes in prescribing behaviour of primary care prescribers. A review in 2012 reported that mailed interventions are well received by prescribers, and are able to evoke significant changes in prescribing patterns [ 30 ]. This finding is encouraging and illustrates the potential in using feedback to drive prescribing performances in primary care through benchmarking among prescribers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that mailed personalised feedback could lead to meaningful changes in prescribing behaviour of primary care prescribers. A review in 2012 reported that mailed interventions are well received by prescribers, and are able to evoke significant changes in prescribing patterns [ 30 ]. This finding is encouraging and illustrates the potential in using feedback to drive prescribing performances in primary care through benchmarking among prescribers.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although evidence of their effectiveness is mixed, 12,13 in some settings, drug utilization review may improve prescribing practices. [14][15][16] We evaluated the impact of a physician-directed drug utilization review on the potentially inappropriate use of controlled substances among members whose claims history suggested high-risk utilization.…”
mentioning
confidence: 99%
“…These interventions show a modest but statistically significant positive effect on changing professional behaviours but the heterogeneity of the trials prevents solid conclusions to be drawn [35, 41, 4652]. Although audit and feedback on test ordering behaviour embedded in peer review in small groups has been found to be more effective than audit and feedback alone, it generally remains unclear exactly what factors contribute to this effect [10, 21, 53, 54].…”
Section: Discussionmentioning
confidence: 99%